2013
DOI: 10.5457/p2005-114.66
|View full text |Cite
|
Sign up to set email alerts
|

The effect of empathy on involving in bullying behavior

Abstract: The aim of this review was to provide an overview of research into the relationship between empathy and bullying. Therefore the review indicated a number of researches that show different effects of empathy on bullying, regarding the type of bullying, roles in bullying behavior, as well as gender. From a review of research it may be concluded that empathy significantly contributes to a reduction in various forms of violence. Most research indicates the importance of the affective component of empathy compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…Some studies show that young defenders have a high level of empathy toward victims, particularly the affective component, which contributes to pro-social behavior (Davis, 1994). Activities in this part of the program make use of those cognitive and affective empathy techniques which have been successfully used in education and training to increase positive interpersonal attitudes in different social contexts (Batson et al, 1997;Dodaj. Sesar, Barisic, & Pandza, 2012;Wo´jcik & Popiolek, 2014).…”
Section: Part 3-empathetic Perception Of Excluded Individualsmentioning
confidence: 99%
“…Some studies show that young defenders have a high level of empathy toward victims, particularly the affective component, which contributes to pro-social behavior (Davis, 1994). Activities in this part of the program make use of those cognitive and affective empathy techniques which have been successfully used in education and training to increase positive interpersonal attitudes in different social contexts (Batson et al, 1997;Dodaj. Sesar, Barisic, & Pandza, 2012;Wo´jcik & Popiolek, 2014).…”
Section: Part 3-empathetic Perception Of Excluded Individualsmentioning
confidence: 99%
“…The results of the research on the relationship between empathy and bullying are less consistent and may differ according to assessment methods, participants' gender or components of empathy. Recent literature reviews have shown that most studies found a negative correlation between cognitive and, in particular, affective empathy and overall bullying (22,23). Less is known about the association of empathy with different bystander roles.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, skills training should include approaches that are affective and relationally based (Heidgerken et al 2004). Developing skills of empathising is an important foundation for planning interventions as the affective component of empathy plays an important role in bullies' behaviour (Dodaj et al 2013). Parent guidance and intervention programmes should focus on multiple aspects of parenting such as monitoring, nurturing, clear communication about norms and expectations for early-adolescent behaviour (Windle et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In bullies the affective component of empathy plays an important role in their behaviour. (Dodaj et al 2013).…”
Section: Future Researchmentioning
confidence: 95%